Private Tutoring during Crisis: Lessons Learned from a Private Tutoring Provider in Indonesia - Yanda, Fikri; Ismail, Lutfi; Anita, Anita; Ayuningtyas, Lidya Pawestri (Journal of Nonformal Education, 2022)
While educational institutions worldwide have been widely affected by the crisis brought about by the COVID-19 pandemic, private tutoring (PT) providers have also profoundly impacted. The only way for survival is to shift to online services, although they have to compete with formal educational institutions that also provide online learning and teaching to the students –customers to the PT providers. The current paper explores the impacts of the COVID-19 pandemic to an English PT provider in Indonesia; how they negotiate and adapt to such a critical circumstance; and what strategies they have to take to sustain their place within the PT sector. Implications and recommendations are also provided.